Scaffolds for liver tissue engineering: in vitro co-culture & in vivo release - Hammond, John Stotesbury (2009)
This thesis presents the development and evaluation of two applications for scaffolds in the field of liver tissue engineering. In the first study a poly (D,L lactic acid) (PDLLA) scaffold is used as a three-dimensional template for hepatocyte–hepatic stellate cell (HSC) co-culture. To enhance PDLLA ligand binding capacity scaffolds are surface modified using allylamine plasma deposition and treatment with NaOH. Primary adult rat hepatocytes and HSC are then seeded onto these scaffolds and cultured in static conditions. Scanning electron microscopy (SEM) is used to assess mono-culture and co-culture morphology whilst synthetic and cytochrome P450 function are measured using albumin and testosterone assays.